Study of knowledge, attitude and practice of copper T as a method of contraception among antenatal women - Malhan, Richa; Nath, Jayati; Bhusan, Anil K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Family planning is defined by WHO as a way of thinking and living that is adopted voluntarily, upon the basis of knowledge, attitudes and responsible decisions by individuals and couples, in order to promote the health and welfare of family groups and thus contribute effectively to the social development of a country. The main objective was to assess the knowledge, attitude and practice regarding family planning and the practice of contraceptives among the antenatal women. Methods: A hospital based, cross sectional study was conducted in obstetrics and gynaecology department of SGT medical college, hospital and research institute over a period of 6 months. Convenient sampling was used to identify and interview 500 pregnant women, using a semi structured questionnaire. Data was entered and analysed with SPSSv21. Results: In our study, 74.2% participants have the knowledge about Cu-T as a method of contraception and 39% participants considered it a safe and economical method of contraception, 16.2% participants used PPIUCD and 40.2% considered it as unsafe method. Uses of PPIUCD was significantly associated with increasing age, illiteracy and non-working participants. Around one third participants were having uncertain attitude towards use of PPIUCD. Conclusions: In our study we observed that uses of PPIUCD is still lower side and there is a need to be motivate the people for effective and appropriate use of contraceptives when required and arrest the trend towards unwanted pregnancy.